Factors affecting employee turnover intention among generation Y workers in fast-food industry / Nurfarahanim Mohammad Fariz and Fadilah Puteh - Mohammad Fariz, Nurfarahanim; Puteh, Fadilah (2021)
In a more advanced technology era, employees remain an important asset and component in operating an organization. However, employee turnover is still a prevalent problem, although most organizations implement appropriate action to prevent employees from quitting their jobs (Arshad & Puteh, 2015). The turnover rate among Gen Y also known as Millennials employees is higher as opposed to Gen X (Hassan et al., 2019; Othman et al., 2017; Queiri et al., 2015). Employee turnover brings negative implications to the organization in terms of expensive HR costs involving processes in replacement employees that leave the organization (Alkahtani, 2015). The National Employment Returns (NER) reported a 20% of turnover rate for the years 2018 and 2019 in various sectors. In addition, accommodation and food activities, a subsector in the service industry shows the highest turnover rate with 30% and 45% in 2018 and 2019 respectively. This means that nearly one in every two employees in the sector quit within a year (Institute of Labour Market Information and Analysis (ILMIA), 2019). The fast-food restaurant is one of the important contributors to Malaysia's economic growth (Bakar, Anuar, Alias, & Mohamad, 2017). Beverages and accommodations, subsectors under the service industry which represent hospitality is the essential economic contributor globally as well as in Malaysia (Kamaruddin & Shamsudin, 2021); are greatly affected by employee turnover (Abo-Murad & AL-Khrabsheh, 2019; Shah & Beh, 2016). Therefore, reducing employee turnover is the main priority, as it disrupts the growth of Malaysia’s economic landscape.